The association between family relationship, deviant peer socialization, self-concept and aggressive behavior among at-risk student in Selangor - Zakaria, Patonah; Md. Noor, Amna; Mohd Khir, Azlina; Wan Jaafar, Wan Munira; Hassan, Mohammad Mujaheed (Human Resource Management Academic Research Society, 2021)
A total of 400 student with disciplinary problem aged 13 to 18 years old from eight secondary schools in the state of Selangor were chosen using multi-stage cluster sampling. A set of questionnaires which are consists of social demographic background, family Relationship Characteristics scale, Peer Deviancy Scale, Self-concept scale and Aggression Scale were used to collect the data. Findings revealed that majority of respondents show the moderate level of self-concept, family relationship, and aggressive behavior and low level of deviant peer socialization. The results of t-test showed that there were significant differences in family beliefs, family structure and deviant peers socialization based on gender and age. There were significant differences in aggressive behavior based on gender, while self-concept has significant differences based on age. Findings also indicated that family relationship, self-concept, deviant peer socialization have a significant relationship with the aggressive behavior. The multiple regression analysis showed that sex, deviant peer socialization, family structure and self-concept have significantly predicted aggressive behavior and socialization of deviant peers was the most important predictor, followed by family structure, self-concept, and sex. The results of this study have important implications for those involved in school and adolescents’ systems.